Progress of estrogen receptor and spliceosome in endometrial carcinoma - Hong, Ziqi; Mo, Ting; Zhou, Peiquan; Chen, Jian; Li, Xin (Frontiers in Endocrinology, 2025)
Endometrial cancer (EC) is one of the most common gynecological cancers in developed countries. Like EC, most female reproductive tract malignancies are thought to be hormonally driven, with estrogen signaling acting as an oncogenic signal. The actions of estrogen are mediated through the classical nuclear estrogen receptors α (ER-α) and β (ER-β) as well as transmembrane G protein-coupled estrogen receptors (GPR30 and GPER). Ligand-bound estrogen receptor (ER) and GPER trigger multiple downstream signaling pathways that regulate the cell cycle, differentiation, migration, and apoptosis in various tissues, including the endometrium. Additionally, growing evidence suggests that selective splicing events at the receptor result in multiple ERα proteins with different molecular weights and functional structural domains. Examples include ER-α66, ER-α46, and ER-α36. In addition, various post-translational modifications (PTMs) further affect ER-α cellular localization and ligand affinity, resulting in a change in the cellular function. These splice isoforms and PTMs are differentially expressed in a tissue-specific manner. They mediate some aspects of ER-α signaling and may even antagonize full-length ER-α. Therefore, both ER-α and its splice isoforms may play a role in the development of EC. In this review, we examine the influential roles of ER-α and ER-β, as well as the GPER estrogen signaling pathway, in EC. Our goal is to provide theoretical support for further research on the molecular mechanisms between ER and EC and to generate new ideas for the early diagnosis of EC and the development of new drugs.